2014
DOI: 10.1074/jbc.m113.543710
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation Decreases Ubiquitylation of the Thiazide-sensitive Cotransporter NCC and Subsequent Clathrin-mediated Endocytosis

Abstract: Background:The sodium chloride cotransporter NCC mediates NaCl reabsorption in the kidney distal convoluted tubule. Results: NCC internalization from the plasma membrane is clathrin-mediated and regulated by NCC phosphorylation and ubiquitylation. Conclusion: Phosphorylation of NCC can regulate NCC internalization and ubiquitylation. Significance: Impaired NCC endocytosis could be implicated in salt-sensitive hypertension in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 53 publications
8
63
2
Order By: Relevance
“…This adds to the evidence that SPAK-mediated phosphorylation acts primarily to increase activity of individual cotransporters without affecting the amount of NCC on the surface (16,19,21). However, there is also evidence in the literature that phosphorylation can affect surface expression (12,24). A recent study demonstrated that phospho-mimicking NCC mutants (replacing T53, T8, and S71 with aspartic acids) have reduced endocytosis resulting in greater surface expression compared with wild-type NCC.…”
Section: Discussionmentioning
confidence: 85%
“…This adds to the evidence that SPAK-mediated phosphorylation acts primarily to increase activity of individual cotransporters without affecting the amount of NCC on the surface (16,19,21). However, there is also evidence in the literature that phosphorylation can affect surface expression (12,24). A recent study demonstrated that phospho-mimicking NCC mutants (replacing T53, T8, and S71 with aspartic acids) have reduced endocytosis resulting in greater surface expression compared with wild-type NCC.…”
Section: Discussionmentioning
confidence: 85%
“…It has been reported that the SPAK-induced phosphorylation of NCC inhibited ubiquitylation of the thiazide-sensitive NCC in the DCT. 41 Although the disruption of cav-1 reduced the expression of NCC, the net renal Na + excretion was not significantly larger in cav-1 KO mice than in WT mice. It is possible that a decrease in NCC expression in the DCT should increase Na + delivery to the CNT/CCD, thereby stimulating Na + absorption through ENaC in these nephron segments, thereby offsetting the effect of low NCC expression.…”
Section: +mentioning
confidence: 99%
“…Evidence suggests that NKCC2 phosphorylation at the serine/threonine residues in the amino-terminal domain (Thr-95, Thr-100, and Thr-105 of human NKCC2), which are conserved in NCC and NKCC1, activate the cotransporter (46, 47, 106); however, it is unclear whether phosphorylation of these residues is associated with activation of the cotransporter that is already in the plasma membrane and/or upregulation of the NKCC2 in the apical membrane. In this regard, data from NCC studies strongly suggest that SPAK/ OSR1 phosphorylates the cotransporter that is already in the plasma membrane, and the phosphorylated transporter becomes resistant to ubiquitylation and clathrin-related endocytosis, ultimately increasing the NCC expression in the plasma membrane (99,118). Given the similarities between NCC and NKCC2, it is possible that a similar mechanism applies for NKCC2.…”
Section: F135 Slc12 Cotransporters In the Kidneymentioning
confidence: 99%
“…The K ϩ modulation of NCC activity has gained much attention (28, 100) because it raised questions about the previously accepted role of aldosterone in stimulating NCC expression/activity (6, 61). It is known that NCC can be regulated by ubiquitylation (63,118), which can occur via the HECT-E3 ligase Nedd4-2 (5) or through modulation of WNK1 ubiquitylation (119). However, aldosterone administration increases urinary K ϩ loss, which, in turn, will reduce serum K ϩ levels and, thus, stimulate NCC activity.…”
Section: F137 Slc12 Cotransporters In the Kidneymentioning
confidence: 99%